Large-scale inhomogeneities may improve the cosmic concordance of supernovae - Amendola, Luca (Physical review letters, 2010)
We reanalyze the supernova data from the Union Compilation including the weak-lensing effects caused by inhomogeneities. We compute the lensing probability distribution function for each background solution described by the parameters ΩM, ΩΛ, and w in the presence of inhomogeneities, approximately modeled with a single-mass population of halos. We then perform a likelihood analysis in the parameter space of Friedmann-Lemaître-Robertson-Walker models and compare our results with the standard approach. We find that the inclusion of lensing can move the best-fit model significantly towards the cosmic concordance of the flat Lambda-Cold Dark Matter model, improving the agreement with the constraints coming from the cosmic microwave background and baryon acoustic oscillations.